Prevalence of HIV and Malaria parasites co-infection in pregnant mothers and their babies post delivery (2013)
Worsened perinatal outcomes and increased rates of maternal morbidity are consequences of co-infection of HIV and Plasmodium falciparum in pregnant-women. This study was designed to ascertain the proportion of co-infection of both diseases in pregnant mothers and babies born to HIV-infected mothers. A total of 149 pregnant mothers and 30 babies of HIV-infected mothers were engaged in a longitudinal study for 18 months in the endemic area of Saki and Ibadan. Only babies born to HIV infected mothers were enrolled and systematically followed-up for six months post delivery. Determine and Unigold rapid diagnostic tests kits were used for HIV test in mothers whereas HIV screening was conducted on the babies using polymerase chain reaction at six months post delivery. Giemsa stained thick blood smear was used to determine the presence of asexual stages of Plasmodium falciparum. Descriptive statistics was used to determine the percentage of infections status. Chi-square and student t-test was used to compare maternal data and babies six months after birth. The results showed that 85/149(57.0%) mothers and 11/30(36.7%) babies, had microscopically detectable malaria parasites whereas the seroprevalence were 64(33.0%) and 19(10.7%) for mothers and infants respectively. In mothers, 19(12.8%) had HIV alone, 51/149(34.2%) malaria only, 34/149 (22.8%) were co-Infected and 45/149(30.2%) had neither HIV nor malaria. In infants, 9/30 (30.0%), 10/30(33.3) had HIV only, 2/30(6.7%) had malaria only whereas 9/30(30.0%) had neither malaria nor HIV. Parasitemia ranged between 251.5 of cells/μL, in mothers and 205.7 of cells/μL, in babies born to HIV infected mothers.